Study of the relationship between mesiodistal angulation of the first molars and mandibular rotation using three-dimensional cephalometric analysis - رمضان, حامد; عبد الكريم حسن (Latakia University Journal -Medical Sciences Series, 2024)
Aim: To Study the effect of mandibular rotation on the mesiodistal angulation of the first molars using cone-beam computed tomography. Materials and Methods: This study was designed as a retrospective radiographic study and the study sample included 30 patients with skeletal class I. Measurements were assessed using three-dimensional cephalometric analysis and cone beam computed tomography. Results: It was found that the mesiodistal angulation of the lower and upper first molars sloped with mandibular rotation, where the angles of the first molars increased as the angle of the mandibular plane (mandibular rotation) increased and this increase was significant. Conclusions: The study found a linear regression relationship between the mesiodistal angulation of the lower and upper first molars and the mandibular plane angle, which means that the angulation of the first molars compensated for mandibular rotation. Keywords:3D-Analysis, Mesiodistal Angulation, Mandibular rotation, Cone Beam Computed Tomography, First Molars.